2010
DOI: 10.2214/ajr.09.3130
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fatty Degeneration of Thigh Muscles and Vitamin D Status in the Elderly: A Preliminary MRI Study

Abstract: In elderly adults, fatty degeneration of thigh muscles was associated with vitamin D deficiency and impaired balance and gait. Selective complete fatty degeneration of single muscles was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 27 publications
2
32
5
1
Order By: Relevance
“…21 In addition, two studies reported an association between low 25(OH)D levels and fatty degeneration of thigh and rotator cuff muscles. 23,24 This potential effect of vitamin D on muscle biology is likely to affect creatinine production. Indeed, an increase in creatininemia due to enhanced creatinine production without variation in GFR has been reported under calcitriol therapy.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, two studies reported an association between low 25(OH)D levels and fatty degeneration of thigh and rotator cuff muscles. 23,24 This potential effect of vitamin D on muscle biology is likely to affect creatinine production. Indeed, an increase in creatininemia due to enhanced creatinine production without variation in GFR has been reported under calcitriol therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy and imaging findings consistent with muscular atrophy have been associated with 25-OH vitamin D deficiency [34,35]. Furthermore, supplementation with calcium and vitamin D improves the number and size of muscle fibers [13] as well as lower extremity function [36].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with mutations of the VDR or severe vitamin D deficiency show generalized muscle atrophy, even before biochemical signs of bone disease appear 36, 47. Changes in muscle morphology include derangement of the intermyofibrillar network, increases in intramuscular lipids, and atrophy of the fast‐twitch white (type 2) fibres,11, 44, 48, 49 which are the first to be recruited when preventing a fall. All these changes seem to be reversible,50 supporting co‐ordinated effects of vitamin D in musculoskeletal physiology 51, 52, 53, 54…”
Section: Vitamin D Physiologymentioning
confidence: 99%